MIWI prevents aneuploidy during meiosis by cleaving excess satellite RNA. (17th July 2020) - Hsieh, Chia‐Ling; Xia, Jing; Lin, Haifan
Abstract: MIWI, a murine member of PIWI proteins mostly expressed during male meiosis, is crucial for piRNA biogenesis, post‐transcriptional regulation, and spermiogenesis. However, its meiotic function remains unknown. Here, we report that MIWI deficiency alters meiotic kinetochore assembly, significantly increases chromosome misalignment at the meiosis metaphase I plate, and causes chromosome mis‐segregation. Consequently, Miwi ‐deficient mice show elevated aneuploidy in metaphase II and spermatid death. Furthermore, in Miwi ‐null and Miwi slicer‐deficient mutants, major and minor satellite RNAs from centromeric and pericentromeric satellite repeats accumulate in excess. Over‐expression of satellite repeats in wild‐type spermatocytes also causes elevated chromosome misalignment, whereas reduction of both strands of major or minor satellite RNAs results in lower frequencies of chromosome misalignment. We show that MIWI, guided by piRNA, cleaves major satellite RNAs, generating RNA fragments that may form substrates for subsequent Dicer cleavage. Furthermore, Dicer cleaves all satellite RNAs in conjunction with MIWI. These findings reveal a novel mechanism in which MIWI‐ and Dicer‐mediated cleavage of the satellite RNAs prevents the over‐expression of satellite RNAs, thus ensuring proper kinetochore assembly and faithful chromosome segregation during meiosis. Synopsis: Major and minor satellite RNAs binding to centromeric and pericentromeric heterochromatin needs to be restrained to ensure proper kinetochore assembly and faithful chromosome segregation during meiosis. The MIWI‐piRNA complex and Dicer cleave excess satellite RNAs, explaining the meiotic role of this meiosis‐specific PIWI protein in mice. MIWI‐deficient spermatocytes over‐accumulate major and minor satellite RNAs. MIWI‐deficient spermatocytes display increased kinetochore mis‐assembly, chromosome misalignment, and exacerbated aneuploidy. Over‐expression of satellite RNAs increases meiosis I chromosome misalignment in wild‐type spermatocytes. The MIWI‐piRNA complex cleaves major satellite RNAs to prevent their over‐accumulation. Satellite RNA accumulation is further reduced by Dicer cleavage of MIWI/piRNA‐generated short RNAs and double‐strand satellite RNAs. Abstract : MIWI/piRNA/Dicer‐mediated cleavage of excess satellite RNAs bound at centromeric and pericentromeric heterochromatin ensures proper meiotic chromosome segregation.